Brønsted acid-catalyzed phenylselenenylation of internal olefins. Issue 19 (6th May 2015) - Wu, Ping; Huang, Fei; Lou, Jiang; Wang, Quannan; Liu, Zhuqing; Yu, Zhengkun
Graphical abstract: Abstract: Brønsted acid p -TsOH·H2 O-catalyzed phenylselenenylation of α-oxo ketene dithioacetals was efficiently achieved by using N -phenylselenophthalimide ( N -PSP) as the phenylseleno reagent. The resultant selenated ketene dithioacetals reacted with styrene in the presence of the same acid to undergo PhSe group transfer, regioselectively affording Markovnikov-type PhSe-alkylated olefins. Their further transformation with phenylboronic acid, guanidine, and hydrazine offers a promising route to access S, Se-incorporated organic compounds.